2007
DOI: 10.1590/s0074-02762007000800005
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of microorganisms from the gut diverticulum of Aedes aegypti (Diptera: Culicidae): new perspectives for an insect-bacteria association

Abstract: We show for the first time that the ventral diverticulum of the mosquito gut (impermeable sugar storage organ) harbors microorganisms. The gut diverticulum from newly emerged and non-fedAedes aegypti (Diptera: Culicidae, Aedini) is the main urban vector for the human diseases yellow fever and dengue fever (Nasci & Miller 1996). The vector control, mainly by insecticide application and elimination of oviposition sites, has been used as the best solution to decrease the diseases incidence. Explore new strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 30 publications
4
91
0
4
Order By: Relevance
“…These results agree with those of other studies where M. caribbica and other species associated with the M. guilliermondii phylogenetic group were isolated from the gut of members of the order Coleoptera (Rao et al, 2007;Hammons et al, 2009;Rivera et al, 2009). Some studies have also reported the isolation of M. caribbica from other sources, such as the digestive tract of Aedes aegypti (Gusmão et al, 2007) and fermented beverages (Papalexandratou and Vuyst, 2011;Hidalgo et al, 2012). M. guilliermondii has also been isolated as an endophytic yeast (Zhao et al, 2010) from bovine milk (Zaragoza et al, 2011) and the genital tract of female camels (Shokri et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with those of other studies where M. caribbica and other species associated with the M. guilliermondii phylogenetic group were isolated from the gut of members of the order Coleoptera (Rao et al, 2007;Hammons et al, 2009;Rivera et al, 2009). Some studies have also reported the isolation of M. caribbica from other sources, such as the digestive tract of Aedes aegypti (Gusmão et al, 2007) and fermented beverages (Papalexandratou and Vuyst, 2011;Hidalgo et al, 2012). M. guilliermondii has also been isolated as an endophytic yeast (Zhao et al, 2010) from bovine milk (Zaragoza et al, 2011) and the genital tract of female camels (Shokri et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the occurrence of Candida and Pichia yeasts has been recorded in Aedes mosquitoes [30, 56,57]. A study confirmed the presence of Candida sp.…”
Section: Yeast Symbionts and Mosquitoes: A New Field Of Investigationmentioning
confidence: 83%
“…Ignatova et al (1996) documented the isolation of certain Candida spp. from different mosquito species and recently, several members of Pichia and Candida genera have been found in the intestinal tract of the species Aedes aegypti (Gusmão et al 2007(Gusmão et al , 2010, the mosquito vector of several viral infections including dengue and yellow fever. A major knowledge of the mosquito yeast microflora could clarify if specific roles described in other insect endosymbiotic yeast relationships maybe relevant for mosquitoes as well.…”
Section: Introductionmentioning
confidence: 99%